Percutaneous medical liver core biopsies: correlation between tissue length and the number of portal tracts. Issue 7 (24th May 2010) - Chan, James; Alwahab, Yasir; Tilley, Charles; Carr, Norman
Abstract : Objective: Liver biopsy is an important tool for the diagnosis and assessment of liver disease. The authors aimed to establish the relationship between biopsy length and the number of total portal tracts. Methods: The authors reviewed 163 16G percutaneous medical liver biopsies taken at a tertiary referral centre over a 14-month period. Haematoxylin and eosin sections were analysed using imaging software and portal tracts were counted. Results: Liver biopsy length correlates with total portal tracts. The median biopsy length was 13.3 mm with a median of six portal tracts. Ninety-five per cent of biopsies measuring at least 15 mm contained six portal tracts or more with a significant difference between total portal tracts when compared with biopsies <15 mm (p<0.0001). Conclusion: To facilitate adequate histological assessment by examining at least six portal tracts, the authors suggest that 16G biopsies should be at least 15 mm long.